Endometriosis of Terminal Ileum: A Case Report - Khan, Mumtaz (Journal of Postgraduate Medical Institute, 2025)
Endometriosis is the result of presence of endometrial tissue at sites other than uterus. A 34 years old female is reported who presented with clinical features of intestinal obstruction. Her abdomen was distended and she was mild tender all over the abdomen. Plan X-ray showed distended small gut loops with air fluid levels. CT reported air fluid levels in small and large bowel with no definite point of transition and mild abdomino-pelvic ascites. In view of suspicion of neoplastic pathology; the patient and her attendants were counseled for exploratory laparotomy. At surgery tight stricture was found at the terminal ileum. Right hemicolectomy was done. The patient had an uneventful recovery.